The Effectiveness of the Movement Method in Enhancing Qur'an Memorization and Comprehension in Preschool Children: A Case Study at TK (Preschool) Al-Fatihah School - Hafidhoh, Husnul; Fatahillah, Mubarok; Maoti, Manapiyah (MyResearch ID Publishing, 2024)
Purpose – This study explores the effectiveness of a movement-based approach to Qur'anic memorization among preschool children at TK (Preschool) Al-Fatihah School. Recognizing the critical role of early childhood in developing a strong attachment to the Qur'an, this research addresses the need for innovative methods that engage children both cognitively and physically, with the goal of enhancing their memorization and understanding of Qur'anic verses. Methods/Design/Approach – A qualitative case study methodology was employed, focusing on 60 preschool children divided into an experimental group (n=30) and a control group (n=30). Data collection methods included participant observation, in-depth interviews with students, teachers, and parents, and document analysis. Thematic analysis was used to identify patterns in student engagement, memorization performance, and understanding of the Qur'anic verses. Findings – The study found that the movement-based method significantly improved students' engagement and memorization. The experimental group memorized 15% more verses on average compared to the control group and demonstrated better long-term retention and fewer errors. Additionally, this method enhanced students' understanding of the verses, as the movements were designed to reflect the meanings of the words, facilitating deeper cognitive processing. Originality/Value – This research contributes to the literature on Qur'anic education by demonstrating that movement-based memorization not only improves the quantity and accuracy of memorization but also enriches students' conceptual understanding. It underscores the importance of integrating physical activity with cognitive learning in early childhood education, particularly in religious contexts. Practical Implications – The findings suggest that movement-based methods can be effectively integrated into Islamic preschool curricula to enhance Qur'anic memorization and comprehension. This approach fosters a more inclusive and engaging learning environment, catering to various learning styles and promoting sustained interest in Qur'anic studies. Keywords Qur'anic memorization, movement-based learning, early childhood education, Islamic education, cognitive development Paper type Research paper